Influence of Biological Parenting, Kinship Care and Geographical Location on Altruistic Behaviour in a Nigerian Sample. - Nwosu, Harry Obi; Diana, Onwukwe; Sebastine, Anaekwe (Advances in Social Sciences Research Journal, 2015)
Altruism may best be described as an unselfish behaviour, attitude and concern towards the welfare of others. It is a form of prosocial behaviour, which is of obvious importance to the quality of interactions between individuals and among groups in the society. However, people have been particularly intrigued with the causes of altruism, hence; researchers have come forth with different approaches to explain the underlying or causative factors of altruistic behaviours. In this study, the researchers examined the influence of factors such as biological parenting, kinship care and geographical location on altruistic behaviour. A 26-item questionnaire comprising of two sections was used and data was gathered from 563 undergraduates of Nnamdi Azikiwe University, Awka. Of the sample, 275 (48.8%) were females and 288 (51.2%) were males with their age ranging from 16-44 years. The Independent group and 2X2 factorial designs were employed in testing the hypotheses. Results showed that students raised by both biological parents were more altruistic than those raised by a single biological parent and that students who lived in rural areas were more altruistic than their urban counterparts. No significant difference was found in altruistic behaviour between students raised by kins and those raised by their parents. Keywords: Altruistic behaviour, biological parenting, kinship care and geographical location.